Implementasi Pembelajaran Bahasa Inggris di SDN 1 Cigembor - Vera Rachmidiana; Erwin Rahayu Saputra (Universitas Pendidikan Indonesia (UPI), 2023)
Reflection in learning is one of the most important activities for both prospective teachers and teachers. The existence of reflection makes an improvement in how he should teach, finds real problems and ways to overcome them, and reviews methods, models, and approaches that are appropriate to the conditions of students. The purpose of this study was to find out the results of reflection on the implementation of teaching practices by researchers as part of the process of implementing English learning courses in elementary schools. The research method used is a qualitative descriptive approach. The results of this study show that the learning process in class IV at SDN 1 Cigembor runs smoothly according to the lesson plans. The implication of this research is that the practice of teaching English in elementary schools can train and hone the abilities of prospective teachers so that they can prepare themselves to become real teachers so that they become real images for subsequent teaching.